Opportunities and limits of open partial horizontal laryngectomies for naïve T3–T4a laryngeal cancer: a systematic review and meta-analysis - Crosetti, Erika; Lorenzi, Andrea; Prizio, Carmine; Sprio, Andrea Elio; Fantini, Marco; Azizi Semeskandi, Alice; Bertolin, Andy; Arrigoni, Giulia; Succo, Giovanni (Frontiers in Oncology, 2025)
BackgroundThe present systematic review aims to investigate the survival rates and surgical outcomes of patients with treatment‐naïve, intermediate (T3) to early advanced (T4a) laryngeal squamous cell carcinoma (LSCC) managed with open partial horizontal laryngectomies (OPHLs).MethodsA systematic literature search was conducted in PubMed, Embase, and Scopus for studies published between January 2000 and December 2023. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Inclusion criteria were: patients with histopathological confirmed LSCC; tumor classified as T3 or T4a stage according to the American Joint Committee on Cancer (AJCC) staging system; having undergone OPHL as the primary treatment without any prior therapy; availability of at least one of the following outcomes: overall survival (OS), disease-specific survival (DSS), disease-free survival (DFS), local control (LC), locoregional control (LRC), laryngectomy-free survival (LFS), and laryngo-esophageal dysfunction-free survival (LEDFS).ResultsA total of 16 studies were deemed eligible for the qualitative analysis. The cumulative number of patients was 1473. The sample size ranged from 17 to 390 patients. The follow-up period ranged from 0 to 198 months. In patients treated with OPHL for T3, the overall five-year pooled proportions were OS 0.82, DSS 0.88, DFS 0.80, and LFS 0.86, whereas for the T4a case series, they were OS 0.77, DSS 0.89, DFS 0.74, and LFS 0.78.ConclusionsOPHL for selected T3 and low extralaryngeal volume T4a LSCC can guarantee a high rate of oncological success. Accurate patient selection is paramount to differentiate advanced diseases that is amenable to conservative surgery.